2008
DOI: 10.1016/j.ajhg.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

CC2D2A Is Mutated in Joubert Syndrome and Interacts with the Ciliopathy-Associated Basal Body Protein CEP290

Abstract: Joubert syndrome and related disorders (JSRD) are primarily autosomal-recessive conditions characterized by hypotonia, ataxia, abnormal eye movements, and intellectual disability with a distinctive mid-hindbrain malformation. Variable features include retinal dystrophy, cystic kidney disease, and liver fibrosis. JSRD are included in the rapidly expanding group of disorders called ciliopathies, because all six gene products implicated in JSRD (NPHP1, AHI1, CEP290, RPGRIP1L, TMEM67, and ARL13B) function in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(211 citation statements)
references
References 46 publications
3
206
1
Order By: Relevance
“…15 In fact, mutations in MKS genes have been reported to cause other ciliopathies, for example, MKS1 and BardetBiedl syndrome, 16 TMEM216 and Joubert syndrome, 17 TMEM67 and Joubert syndrome and nephrophthisis, 18,19 CEP290 in non-syndromic retinal dystrophy, Senior-Loken syndrome, nephronophthisis, Joubert syndrome, and Bardet-Biedl syndrome, 20 RPGRIP1L and Joubert syndrome, 21 and CC2D2A and Joubert syndrome. 22 The factors that determine the ultimate clinical phenotype are not completely understood but there is growing evidence that ciliopathies represent a spectrum of clinical severity that correlates to some extent with the severity of the ciliary defect. Consistent with MKS being at the severe end of the clinical spectrum, most causative mutations are truncating in nature while hypomorphic mutations in the same genes cause less severe phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…15 In fact, mutations in MKS genes have been reported to cause other ciliopathies, for example, MKS1 and BardetBiedl syndrome, 16 TMEM216 and Joubert syndrome, 17 TMEM67 and Joubert syndrome and nephrophthisis, 18,19 CEP290 in non-syndromic retinal dystrophy, Senior-Loken syndrome, nephronophthisis, Joubert syndrome, and Bardet-Biedl syndrome, 20 RPGRIP1L and Joubert syndrome, 21 and CC2D2A and Joubert syndrome. 22 The factors that determine the ultimate clinical phenotype are not completely understood but there is growing evidence that ciliopathies represent a spectrum of clinical severity that correlates to some extent with the severity of the ciliary defect. Consistent with MKS being at the severe end of the clinical spectrum, most causative mutations are truncating in nature while hypomorphic mutations in the same genes cause less severe phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…43 Mutations in CC2D2A in humans lead to RP, often as part of multi-organ syndromes. [44][45][46] Growth of the microtubule axoneme is dependent on chaperone proteins such as prefoldin-5 that, when mutated in mice, leads to photoreceptor degeneration. 47 Other chaperones including HSC70 (Hspa8) have also been found to be associated with photoreceptor axonemal proteins.…”
Section: Photoreceptor Development and Inherited Retinal Conditionsmentioning
confidence: 99%
“…Today, JSRDs are included in the rapidly expanding group of disorders called ciliopathies, because all six gene products implicated in JSRD (NPHP1, AHI1, CEP290, RPGRIP1L, TMEM67, and ARL13B) function in the primary cilium/basal body organelle (14). Recently Gorden et al (14) identified lossof-function mutations in CC2D2A in JSRD patients with and without retinal, kidney, and liver disease. Conventional cranial MRI features of JSRD are well known today.…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that genetic and environmental factors during this developmental period (most probably between 3 weeks and 26 weeks of gestation) may cause embryological abnormalities, affecting both supra-and infratentorial structures (7). Today, JSRDs are included in the rapidly expanding group of disorders called ciliopathies, because all six gene products implicated in JSRD (NPHP1, AHI1, CEP290, RPGRIP1L, TMEM67, and ARL13B) function in the primary cilium/basal body organelle (14). Recently Gorden et al (14) identified lossof-function mutations in CC2D2A in JSRD patients with and without retinal, kidney, and liver disease.…”
Section: Discussionmentioning
confidence: 99%